Elasticity‐Driven Nanomechanical Interaction to Improve the Targeting Ability of Lipid Nanoparticles in the Malignant Tumor Microenvironment - Eunhee Lee; Loi Nguyen Dang; Jinsol Choi; Haesoo Kim; Lyndon Bastatas; Soyeun Park (Advanced Science, 2025)
Abstract The mechanical elasticity of lipid nanoparticles (LNPs) is crucial to their pharmaceutical performance. This study investigates how the mechanical interactions between LNPs, target cells, and macrophages affect the internalization of LNPs into target cells at tumor sites. According to our bio‐mechanical study, drug‐resistant breast cancer cells are stiffer than sensitive ones, while invasive cells are softer; similarly, protumoral M2 macrophages are softer than M1 macrophages. Softer LNPs show increased cellular uptake in breast cancer cells and macrophages, with enhanced engulfment in invasive cells and M2 macrophages. Additionally, the presence of M2 macrophages promotes greater LNP internalization by cancer cells, facilitating the malignant and invasive nature of cancer cells. In addition, because breast cancer cells engulf LNPs via an energy‐efficient fusion pathway but LNPs in macrophages undergo clathrin‐mediated endocytosis, LNPs are internalized more into cancer cells but not into M2. In orthotopic tumor models, softer LNPs penetrate tumors quickly, enhancing suppression, whereas stiffer LNPs permeate slowly but show prolonged retention in stiffer tumors, supporting antitumor efficacy with repeated dosing. These findings underscore the importance of mechanical interactions between LNPs, target cells, and macrophages in optimizing LNP delivery systems, offering insights for more effective designs.